2015
DOI: 10.3386/w21598
|View full text |Cite
|
Sign up to set email alerts
|

Achievement Effects of Individual Performance Incentives in a Teacher Merit Pay Tournament

Abstract: This paper estimates the effect of the individual incentives teachers face in a teacher-based value-added merit pay tournament on student achievement. We first build an illustrative model in which teachers use proximity to an award threshold to update their information about their own ability, which informs their expected marginal return to effort. The model predicts that those who are closer to an award cutoff in a given year will increase effort and thus will have higher achievement gains in the subsequent y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…6 Plans implemented in the US, however, have yielded mixed results (see Jackson et al, 2014;Neal et al, 2011, for a review). 7 In addition, this paper provides new evidence that school districts are willing to compensate high VA teachers when given the opportunity to do so and that teachers respond to these incentives by exerting more effort in the classroom (Imberman and Lovenheim, 2015;Brehm et al, 2017).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…6 Plans implemented in the US, however, have yielded mixed results (see Jackson et al, 2014;Neal et al, 2011, for a review). 7 In addition, this paper provides new evidence that school districts are willing to compensate high VA teachers when given the opportunity to do so and that teachers respond to these incentives by exerting more effort in the classroom (Imberman and Lovenheim, 2015;Brehm et al, 2017).…”
Section: Introductionmentioning
confidence: 97%
“…6 This literature includes studies conducted in India (Muralidharan and Sundararaman, 2011;Duflo et al, 2012), Israel (Lavy, 2002), England (Atkinson et al, 2009), and Kenya (Glewwe et al, 2010). 7 Although some studies have found that teacher performance pay has positive effects on student test scores in the US (Ladd, 1999;Figlio and Kenny, 2007;Sojourner et al, 2014;Imberman and Lovenheim, 2015;Dee and Wyckoff, 2015;Brehm et al, 2017), others have shown that such incentives are ineffective at boosting achievement (Dee and Keys, 2004;Figlio and Kenny, 2007;Springer et al, 2011;Goodman and Turner, 2013;Fryer, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, lump sum bonuses, incentives and or pay increases are several forms of merit pay have often been provided to high performing employees in organisations (Newman et al, 2017;Martocchio 2016). These pay allocations are very important because they will draw, keep and inspire high performing employees to support workflow, enhance fairness, improve the product and or quality of service and decrease operation costs (Brehm, Imberman & Loveheim 2017;Siti Salwa & Azman 2016). As a result, it may help to accomplish the strategic business vision and missions of both the management of the human resource and the organisation in question (Rozila & Scott 2015;Balkin, Roussel & Werner 2015;Newman et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The existence of a feedback mechanism following each evaluation of teaching practices may allow teachers to update their beliefs and may help them alter their teaching practices. The complex nature of value‐added scores along with a lack of any meaningful feedback are considered among the reasons why teacher incentives fail (Brehm et al., ; Fryer, ). Finally, incentives in Louisiana TAP schools are not weak (reaching 12.5 percent of a beginning teacher's base salary) and the structure of the bonus pay includes both absolute targets and rank‐order tournament and does not necessarily imply egalitarian distributions.…”
Section: Introductionmentioning
confidence: 99%